2010
DOI: 10.1029/2009jc006073
|View full text |Cite
|
Sign up to set email alerts
|

Heat and salt balances over the New England continental shelf, August 1996 to June 1997

Abstract: Heat and salt balances over the New England shelf are examined using 10 month time series of currents, temperature, and salinity from a four element moored array and surface heat and freshwater fluxes from a meteorological buoy. A principal result is closure of the heat budget to 10 W m−2. The seasonal variation in depth‐average temperature, from 14°C in September to 5°C in March, was primarily due to the seasonal variation in surface heat flux and a heat loss in winter caused by along‐shelf advection of colde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…The minimum temperature in the Cold Pool increases steadily from April to September at a rate of 1°C month −1 over the New England shelf. The Cold Pool disappears in fall (October–November) as vertical mixing from increasing storm activity and decreasing surface heat flux destroys the seasonal thermocline [ Lentz et al ., ].…”
Section: Average Seasonal Evolution Of the Cold Poolmentioning
confidence: 97%
See 2 more Smart Citations
“…The minimum temperature in the Cold Pool increases steadily from April to September at a rate of 1°C month −1 over the New England shelf. The Cold Pool disappears in fall (October–November) as vertical mixing from increasing storm activity and decreasing surface heat flux destroys the seasonal thermocline [ Lentz et al ., ].…”
Section: Average Seasonal Evolution Of the Cold Poolmentioning
confidence: 97%
“…The dependence of warming rate on Cold Pool thickness is consistent with (2) (black dashed lines in Figure ) with larger heat fluxes through the thermocline QE over Georges Bank (∼100 W m −2 ) and the New England shelf than in the New York Bight and southern MAB (∼30 W m −2 ). The inferred heat flux through the thermocline over Georges Bank and the New England shelf is a substantial fraction of the net surface heat flux through the sea surface which ranges from 100 W m −2 in spring to a maximum of 200 W m −2 in July and August [ Beardsley et al ., ; Lentz et al ., ; Lentz , ; Fewings and Lentz , ; Georgas et al ., ]. The inferred heat flux through the thermocline in the southern half of the MAB is a smaller fraction of the net surface heat flux.…”
Section: Mean Heat Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The term Cold Pool continues to be used to describe this dynamic feature [13] [4] [2] [3], which is characterized by southwestward advection with an accompanying gradual increase in the heat and salt fluxes through the surface and lateral boundaries [12] [14] [15]. It has been shown that the Cold Pool affects phytoplankton productivity [16] [9] and the behavior and recruitment of pelagic and demersal fish on the shelf [21] [24].…”
Section: Introductionmentioning
confidence: 99%
“…The models produce dynamically consistent output on a regular grid, which greatly facilitates the computation of the mean and eddy fluxes. The basic methodology being used is similar to that used during the CODE experiment [Lentz, 1987;Lentz et al, 2010]. The surface flux computations are complete (see below).…”
Section: Work Completedmentioning
confidence: 99%